The implantation and the consolidation of the industry of confection in the southwestern mesoregion of the Paraná - Migliorini, Sonia Mar dos Santos (UFPR, 2007)
The confection industry was one of the precursory industriesof the process of industrialization of Southwestern Mesoregionof Paraná. This industry began its activities in Mesoregion inthe end of the 1970’s and beginning of the 1980’s. Startingfrom the 1990’s, the number of industrial units have grownimmensely in terms of increase of jobs and income, being partof the industrial sectors with larger economical importance ofthe region. The present article aims at identifying the factorsthat conditioned the implantation of the confection industry inSouthwest Mesoregion of Paraná and their perspectives. Inconclusion, it presents a group of factors that have influencedthe implantation and consolidation of the confection industryin Mesoregion and it evaluates the perspectives of thatregional industry based upon in the study of their competitiveadvantages.